2021
DOI: 10.1177/2150132720987715
|View full text |Cite
|
Sign up to set email alerts
|

Rural Emergency Medical Service Providers Perceptions on the Causes of and Solutions to the Opioid Crisis: A Qualitative Assessment

Abstract: Introduction: The continuing opioid crisis poses unique challenges to remote and often under-resourced rural communities. Emergency medical service (EMS) providers serve a critical role in responding to opioid overdose for individuals living in rural or remote areas who experience opioid overdoses. They are often first at the scene of an overdose and are sometimes the only health care provider in contact with an overdose patient who either did not survive or refused additional care. As such, EMS providers have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This qualitative study provided insights into the experiences of EMS personnel in responding to substance use-related calls, especially during the COVID-19 pandemic on top of the opioid crisis in the US. EMS personnel are critical stakeholders in combating the opioid crisis; they are often the first health care provider called to the overdose scene [ 1 , 23 ]. Therefore, it is essential to understand the needs of EMS personnel directly from them to provide the resources and training needed to address those needs, which our findings provide.…”
Section: Discussionmentioning
confidence: 99%
“…This qualitative study provided insights into the experiences of EMS personnel in responding to substance use-related calls, especially during the COVID-19 pandemic on top of the opioid crisis in the US. EMS personnel are critical stakeholders in combating the opioid crisis; they are often the first health care provider called to the overdose scene [ 1 , 23 ]. Therefore, it is essential to understand the needs of EMS personnel directly from them to provide the resources and training needed to address those needs, which our findings provide.…”
Section: Discussionmentioning
confidence: 99%
“…Even before the pandemic, the opioid crisis in highly impacted rural areas led to the recommendation that TM‐based medication treatment for opioid use disorder (MOUD) might offer a means to expand treatment access and improve retention of MOUD in rural areas 3,4 . Rural communities are of particular concern because they are disproportionately impacted by opioid use disorder (OUD) and encounter many challenges to accessing MOUD (eg, limited availability of MOUD services, economic distress, older populations, social isolation, and travel burden) 5–10 . Studies comparing in‐person and TM‐based MOUD generally showed comparable effectiveness and even better retention outcomes in TM‐based MOUD 11–13 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Rural communities are of particular concern because they are disproportionately impacted by opioid use disorder (OUD) and encounter many challenges to accessing MOUD (eg, limited availability of MOUD services, economic distress, older populations, social isolation, and travel burden). [5][6][7][8][9][10] Studies comparing in-person and TM-based MOUD generally showed comparable effectiveness and even better retention outcomes in TM-based MOUD. [11][12][13] According to a recent study, the policy changes supportive of TM implemented during the COVID-19 pandemic had a positive effect on the access to health care and clinical outcomes of rural patients with OUD.…”
Section: Introductionmentioning
confidence: 99%
“…Rates of opioid overdose deaths have increased in the United States over the past 15 years and continue to rise in the context of the COVID‐19 pandemic 1,2 . Rural communities are of particular concern because they are disproportionately impacted by the opioid crisis and encounter many challenges to accessing medication treatment for OUD (MOUD), such as limited availability of MOUD services, economic distress, older populations, social isolation, and travel burden 3–8 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Rural communities are of particular concern because they are disproportionately impacted by the opioid crisis and encounter many challenges to accessing medication treatment for OUD (MOUD), such as limited availability of MOUD services, economic distress, older populations, social isolation, and travel burden. [3][4][5][6][7][8] Few studies have investigated the prevalence rate of OUD and the rate of MOUD in rural communities. A study that used electronic health records (EHRs) during the years 2014-2016 in 6 urban health care TA B L E 1 Numbers and prevalence rates of patients with OUD and MOUD in the 6 sites during the 15-month study period.…”
Section: Introductionmentioning
confidence: 99%